2021
DOI: 10.1177/25165984211016445
|View full text |Cite
|
Sign up to set email alerts
|

Study of surface crack density and microhardness of Aluminium 6061 alloy machined by EDM with mixed powder and assisted magnetic field

Abstract: Magnetic field assisted powder mixed electrical discharge machining (MFAPM-EDM) has emerged as hybrid electrical discharge machining (EDM) technique which improves machining performance by the addition of powder in dielectric and under the influence of magnetic field. In the present article, Aluminium 6061 alloy was machined through fabricated MFAPM-EDM set-up considering the one-parameter-at-a-time method. The individual effect of process parameters, namely pulse on duration (PON), pulse off duration (POFF), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The experiment yielded an average MRR of 40 µg/min, confirming the Maglev EDM’s capability for micro-hole production on conductive materials. Rouniyar et al 17 introduced MFA powder mixed EDM as an innovative hybrid technique to enhance machining performance by incorporating powder into the dielectric medium and applying an MF. Aluminium 6061 alloy was processed using this setup, with a focus on individual process parameter effects on surface crack density (SCD) and microhardness (MH).…”
Section: Introductionmentioning
confidence: 99%
“…The experiment yielded an average MRR of 40 µg/min, confirming the Maglev EDM’s capability for micro-hole production on conductive materials. Rouniyar et al 17 introduced MFA powder mixed EDM as an innovative hybrid technique to enhance machining performance by incorporating powder into the dielectric medium and applying an MF. Aluminium 6061 alloy was processed using this setup, with a focus on individual process parameter effects on surface crack density (SCD) and microhardness (MH).…”
Section: Introductionmentioning
confidence: 99%
“…However, the work is limited to finish machining regime alone [37]. Authors tried to explore the significance of adding Cr [38], Al 2 O 3 [39], nanoalumina and SiC [40] powders into the liquid dielectric during EDM process. Authors reported that lessened surface cracks were noticed in PMEDMed surface compared to that produced by conventional EDM [41].…”
Section: Introductionmentioning
confidence: 99%
“…AK Rouniyar, P Shandilya [17] studied the micro hardness of EDM machined AA6068. The results concluded that microhardness is increased for machined sample than the parent material which is owing to the carbide and oxide layer formation on the surface, quenching effect.…”
Section: Introductionmentioning
confidence: 99%